The influence of instruction, prior knowledge, and values on climate change risk perception among undergraduates - Aksit, Osman; McNeal, Karen S.; Gold, Anne U.; Libarkin, Julie C.; Harris, Sara (Journal of Research in Science Teaching, 2018)
We evaluated influences on the climate change risk perceptions of undergraduate students in an introductory Earth Science course. For this sample, domain-specific content knowledge about climate change was a significant predictor of students' risk perception of climate change while cultural worldviews (individualism, hierarchy) and political orientation were not. These results contrast with previous studies highlighting worldviews as a dominant influence on risk perception. At the beginning of the semester, students' climate change content knowledge was relatively low, with average scores on a 21-item test less than 50%. Post instruction results indicated that students learned climate change science during the course, and their perceptions of risks associated with climate change increased. Unlike most prior research evaluating links between climate change knowledge and risk perception, our measure of content knowledge was a validated assessment specific to climate change. Use of this specific climate knowledge test may be one reason that we detected a relationship between climate knowledge and risk perception whereas most of the previous research has not. Another—possibly complementary—explanation may be a generational shift between our study sample and prior samples. Undergraduates today, having grown up with more exposure to climate change in schools and the media than previous generations, may be diverging from average adults in that learning climate science appears to also increase their perceptions of the risks climate change poses. Undergraduate courses with embedded climate-related activities present an opportunity to both increase climate science knowledge and risk perceptions of future decision makers.
Keywords: climate change; risk perception; undergraduate students